(untitled) (Research, Society and Development, 2020)
Nursing residents because they are young, newly trained and inexperienced are vulnerable to burnout because they have not developed adaptive mechanisms in front of the stressors present in the training. To verify the occurrence of burnout in resident nurses of specialized units and to analyze the dimensions involved. A cross - sectional study with a sample of 78 resident nurses from specialized units of a public university hospital located in the city of Rio de Janeiro (Brazil). In the data collection, a structured instrument was used to record sociodemographic, occupational, and health data. In the verification of the occurrence of burnout in the sample the Maslach Burnout Inventory-Human Services Survey. Results: The sample consisted mainly of female residents, unmarried, 21 and 25 years of age, newly formed. We verified the occurrence of burnout in 03 residents according to the cutoff points adopted. On the dimensions, high scores were identified for emotional exhaustion (53.8%), medium in depersonalization (60.3%) and high for professional achievement (75.6%). Conclusions: The occurrence of burnout in the sample and the high scores in emotional exhaustion indicate the need to review teaching learning strategies, the structure of the course and the social and technical support of the group.